T Cell-Specific Overexpression of Acid Sphingomyelinase Results in Elevated T Cell Activation and Reduced Parasitemia During Plasmodium yoelii Infection - Hose, Matthias; Günther, Anne; Abberger, Hanna; Begum, Salina; Korencak, Marek; Becker, Katrin A.; Buer, Jan; Westendorf, Astrid M.; Hansen, Wiebke (Frontiers in Immunology, 2019)
The enzyme acid sphingomyelinase (ASM) hydrolyzes sphingomyelin to ceramide and is thereby involved in several cellular processes such as differentiation, proliferation, and apoptosis in different cell types. However, the function of ASM in T cells is still not well characterized. Here, we used T cell-specific ASM overexpressing mice (t-ASM/CD4cre) to clarify the impact of cell-intrinsic ASM activity on T cell function in vitro and in vivo. We showed that t-ASM/CD4cre mice exhibit decreased frequencies of Foxp3+ T regulatory cells (Tregs) within the spleen. Enforced T cell-specific ASM expression resulted in less efficient induction of Tregs and promoted differentiation of CD4+CD25- naïve T cells into IFN- producing Th1 cells in vitro. Further analysis revealed that ASM-overexpressing T cells from t-ASM/CD4cre mice show elevated T cell receptor (TCR) signaling activity accompanied with increased proliferation upon stimulation in vitro. Plasmodium yoelii infection of t-ASM/CD4cre mice resulted in enhanced T cell activation and was associated with reduced parasitemia in comparison to infected control mice. Hence, our results provide evidence that ASM activity modulates T cell function in vitro and in vivo.